The Theoretical Analysis of the Colour Constancy - Breive, K.; Vaitkevicius, H.; Bliznikas, Z.; Viliunas, V.; Svegzda, A. (Elektronika ir Elektrotechnika, 2000)
The possibility of application of the phenomenon of colour constancy for technical purposes is discussed in this paper. The colour constancy is a property of human vision system to perceive colours of the objects regardless of colour of the illuminant.The experimental data for 40 Munsell hues of 7/8 and 40 Munsell hues of 7/4 brightness/saturation from Munsell Colour Atlas were used for analysis. The sources of illuminant of types A, C, b and g were applied in these experiments.The method for numerical evaluation of colour constancy was introduced. It is possible to evaluate separately the physical and subjective changes in hue and subjective changes in saturation of the object's colour when the colour of the illuminant changes by using this method. It was found out, that the process of colour constancy is based on the natural transformation of colour coordinates. The minimal changes in hue is for colour objects, which colour vectors lies in the plane that lies through the origin of L, u', v' coordinates, white point and the point of illuminant coordinates. The minimal changes in saturation is for objects, which colour coordinates in the u', v' colour plane are placed in the direction, perpendicular to line of the illuminant change.